Optical measurement of tissue perfusion in diabetic wound patients - Punai Philimon, Sheena; Huong Kah Ching, Audrey; Ngu, Xavier (Penerbit Uthm, 2019)
Diabetes, a metabolic disease related to high sugar level, has been ranked one of the most common chronic diseases worldwide with a total of 15% diabetic patients developing diabetic foot ulcer each year [1]. The development of foot ulcer is generally linked to the existence of peripheral vascular disease and poor glycemic control which, if left unattended for a prolonged time, would result in osteomyelitis and amputation of the affected foot [2]. This has, thus, placed a sizable burden on patient, healthcare system and society. Awareness on this matter has prompted immediate actions from medical committees to advocate a proper preventive approach on handling patients with diabetic foot ulcer before the condition deteriorates. A clinical instrument for continuous and non-contact assessment of diabetic foot ulcer shown in Figure 1.1 is often desirable to provide information on wound healing progress with different prescribed treatment. This is such that immediate action on changes in the standard clinical treatment may be taken following poor response of ulcer healing progress to prevent further deterioration of wounds, which may lead to foot amputation.